Formation and classification of psychosomatic disorders - Bukataru, Yuliana; Reva, Marina; Berezya, Ksenia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
According to the conceptual provisions of modern integrative psychological medical science, which highlight the features of the classification of psychosomatic disorders, the basic is considered to be three aspects of psychosomatic defects: mental disorders manifested in the somatic sphere, mental disorders formed on the basis of somatic pathology, somatic disorders pathologies, personality anomalies and psychogenic factors. In summary, we can say that the main prerequisites for the formation and manifestation of psychosomatic disorders can be both conditions of psychosocial instability and disorders of major organ systems, such as nervous or endocrine. Researchers also agree that a number of psychosomatic disorders can be inherited, but their manifestation is not mandatory, depending on the environmental factors in which the individual is. Regarding the classification of psychosomatic disorders, there is no single system of classifications, but depending on which criterion is taken as the basis of classification, the most complete can be considered the classification proposed by K. Jaspers, R. Lemke and others. The basis for the classification of psychopathological disorders are signs that are defined as criteria. So the key signs can be: organic symptoms, physiological correlates of anxiety, symptoms that appear during the formation and development of psychosomatic disorders.